Inclusive entrepreneurship as a vector of business development - D. S. Shikhalieva (Путеводитель предпринимателя)
The article examines the role of inclusion in modern entrepreneurship, defines the concept of «inclusive entrepreneurship». The purpose of the study is to consider the theoretical aspects and issues related to the dissemination of inclusive policies in the activities of modern enterprises and organizations. The presented data indicate the need to create equal employment opportunities for socially vulnerable citizens, as well as to propose new approaches to solve the problems of consumers with special needs.